Perkembangan Profil Karakter Jujur Mahasiswa Berbasis Pemikiran Al-Ghazali dan Said Hawa dan Implikasinya Bagi Bimbingan Konseling - Gustini, Neng (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This study aims to identify and describe the honest character of students based on the thoughts of Al Ghazali and Said Hawa. This research approach is quantitative with the descriptive method of comparative technique using a questionnaire instrument, study documentation, and observation. The data collected were analyzed using descriptive statistical techniques and reliability and validity test analysis techniques. Based on the results of quantitative research through reliability and validity tests, we obtained that the honest character data of students were in the reasonably honest category. There was a need for more profound, honest character development in the oral and determination aspects.